2021
DOI: 10.1016/j.asmr.2021.04.004
|View full text |Cite
|
Sign up to set email alerts
|

The FAST Workstation Shows Construct Validity and Participant Endorsement

Abstract: Purpose: To determine in what way the proposed simulation-based intervention (SBI) is an effective intervention for use in basic arthroscopic skills training. Methods: Twenty candidates were recruited and grouped according to experience. Performance metrics included the time to activity completion, errors made, and Global Rating Scale score. Qualitative data were collected using a structured questionnaire. Results: Performance on the SBI differed depending on previous arthroscopic training received. Performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Previous studies have suggested a relation between arthroscopic case experience and improved performance on simulated arthroscopy models, but this relation is not absolute. 22 , 24 , 25 , 26 Our study included a combination of academic, university-based training programs, and we hypothesize that an undertaking involving different types of residency programs would find even more variability in its results. Further research is needed to determine whether performance on the FAST training modules correlates with more direct measures of arthroscopic skill and experience, such as arthroscopic case volume or performance in the operating room.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested a relation between arthroscopic case experience and improved performance on simulated arthroscopy models, but this relation is not absolute. 22 , 24 , 25 , 26 Our study included a combination of academic, university-based training programs, and we hypothesize that an undertaking involving different types of residency programs would find even more variability in its results. Further research is needed to determine whether performance on the FAST training modules correlates with more direct measures of arthroscopic skill and experience, such as arthroscopic case volume or performance in the operating room.…”
Section: Discussionmentioning
confidence: 99%